Neurocognitive mechanisms of the mindfulness based therapy - Moscoso, Manolete S. (2015)
We are presenting an overview and a brief history of the growing field of Mindfulness Based Interventions. There has been a significant interest in this therapeutic model to reduce vulnerability to chronic stress and emotional distress in recent times. Mindfulness requires intentionally bringing our attention to the experiences that occur in the present moment. As the research advances in this line of inquiry, it is vital to carefully define the construct of Mindfulness and better understand its neurocognitive mechanisms of action. This review presents conceptual framework that emphasizes the central role of attentional control and sustainability mechanisms to build mindfulness skills. We also review the construct of Mindfulness and self-regulation of emotions; then describe briefly our research related to our Mindfulness Based-Stress Reduction Breast Cancer (MBSR-BC) program at the University of South Florida. With this premise, we present a model explaining our proposed cognitive mechanisms based on the Logic of the Biobehavioral Model.